Pengaruh Kompensasi Manajemen dan Reputasi Auditor Terhadap Manajemen Pajak pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015 - Sari, Tika Nur Amalina; , Dr. Noer Sasongko, SE.,M.Si., Ak,CA (2017)
This study aimed to examine the effect of audit opinion, solvability, size of public accountant, profit/loss, and complexity of operations of the company to the audit report lag. The research population is manufacturing companies listed in Indonesia Stock Exchange (BEI) in period 2013-2015. Purposive sampling method is used to sampling population. The number of samples taken was 93 companies. Analysis of data using multiple linier regression analysis. The result of the research show that (1) variable audit opinion used negative effects to audit report lag (2) variable solvability used not effect the audit report lag (3) variable size of public accountant used positive effects to audit report lag (4) variable profit/loss not effect the audit report lag (5) variable complexity of operations of the company used not effect the audit report lag. Keyword: audit opinion, solvability, size of public accountant, profit/loss, and complexity of operations of the company, Audit Report Lag